Increasing youth awareness on the election in Baubau City - Eko Satria; Rizki Mustika Suhartono; Edy Nurcahyo; Zubair Zubair; Yayan Sera (Universitas Muhammadiyah Magelang, 2023)
Every action that affects the destiny of the country and its region involves youth. Youth must take the initiative in promoting the value of political awareness in elections to create quality elections without succumbing to rigged elections. This community service aims to increase youth political awareness in preparation for simultaneous general elections 2024 in Baubau City. The political education method is used to carry out this program. The result of this program is that the participants are more aware of the importance of voting rights and participating in the political process, including its stages, the role of each related institution, and the importance of fair and democratic elections.